Antiquus Error/novus error: the HA, Nicomachus Flavianus, and the 'pagan resistance'. - Cameron, Alan (Journal of Roman Archaeology, 2011)
The article reviews the book "'Antiquus Error'. Les Ultimes Feux De La Résistance Païenne. 'Scripta varia' augmentés de cinq études inédites," by Stéphane Ratti, book 14 in the Bibliothèque de l'Antiquité Tardive series.